2018
DOI: 10.1111/ner.12583
|View full text |Cite
|
Sign up to set email alerts
|

Remotely Supervised Transcranial Direct Current Stimulation Increases the Benefit of At-Home Cognitive Training in Multiple Sclerosis

Abstract: Objective To explore the efficacy of remotely-supervised transcranial direct current stimulation (RS-tDCS) paired with cognitive training (CT) exercise in participants with multiple sclerosis (MS). Methods In a feasibility study of RS-tDCS in MS, participants completed ten sessions of tDCS paired with CT (1.5 mA × 20 min, dorsolateral prefrontal cortex montage). RS-tDCS participants were compared to a control group of adults with MS who underwent ten 20-min CT sessions through the same remotely supervised pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 89 publications
1
96
0
1
Order By: Relevance
“…During the 20-minute stimulation period, participants completed cognitive training games targeting processing speed and working memory. 34 …”
Section: Methodsmentioning
confidence: 99%
“…During the 20-minute stimulation period, participants completed cognitive training games targeting processing speed and working memory. 34 …”
Section: Methodsmentioning
confidence: 99%
“…To this end, Charvet and colleagues proposed 8 recommendations, which we followed in this study [29]. The same team applied these principles in a remotely-supervised tDCS randomized clinical trial (RCT) associated with cognitive training in patients with multiple sclerosis [30]. This study showed not only the feasibility of such a design in a large population but also the efficiency of combining tDCS with other rehabilitation procedures as abovementioned.…”
Section: G Martens Et Al / Brain Stimulation XXX (2018) 1e9mentioning
confidence: 97%
“…Charvet et al report on a randomized, open‐label clinical trial in multiple sclerosis patients undergoing either computer‐based cognitive training or cognitive training + tDCS. The combined treatment was superior to cognitive training alone in terms of cognitive processing.…”
Section: Resultsmentioning
confidence: 99%